Pengaruh Kompetensi dan Karakteristik Individu terhadap Kinerja Karyawan pada PT Dhanarmas Concern - Aeni, Puri Nur; Ali, Mochammad Mukti (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
This research aims to analyze the influence of employee competence and individual characteristics on the performance of personnel at PT Dhanarmas Concern. Competence encompassing aspects such as knowledge, technical skills, and professional capabilities along with personal attributes like personality, motivation, and attitude, plays a vital role in shaping work productivity and output quality. The objective of this study is to measure the extent to which both competence and personal characteristics contribute to employee performance, whether jointly or individually. A quantitative research method was employed, supported by a survey technique. Data collection was carried out using a structured questionnaire distributed to 15 employees at PT Dhanarmas Concern. The selection of respondents was conducted using a simple random sampling method. In this study, employee competence and individual characteristics serve as independent variables, while employee performance functions as the dependent variable. To examine the correlation and effect between these variables, the data was analyzed using appropriate statistical techniques.